Locating the People: An Exploration of Non-Resident Enfranchisement and Political Belonging in Frank v. Canada (Attorney General) - Burton, Sarah (McGill Law Journal / Revue de droit de McGill, 2021)
This piece situates non-resident voting within the larger divide between global and local values. The Supreme Court of Canada held in Frank v. Canada (Attorney General) that disenfranchising certain non-resident citizens violated the Canadian Charter of Rights and Freedoms. I argue that this opinion is driven by a disagreement on the meaning of belonging, in which the constitutional status of non-resident citizens is emblematic of broader questions about political membership in a globalized world. Non-resident voting offers a compelling case study, in which theoretical attempts to reconcile global and local values are exposed as having unexpected contours. The Supreme Court majority’s global stance is notably patriotic, while the dissent’s call for local connections unwittingly brings it in line with cosmopolitan thinkers. These insights offer a better understanding of the strands of thought within the global-local divide and highlight the nebulous nature of arguments based in political belonging.